Nanostructuring and Phase Transformations in the β‐Alloy Ti‐15Mo during High‐Pressure Torsion1. Issue 12 (30th September 2015) - Gatina, Svetlana; Semenova, Irina; Leuthold, Jörn; Valiev, Ruslan
Abstract : In this paper, the processes of grain refinement and phase transformations in the Ti‐15Mo β‐alloy during high‐pressure torsion (HPT) at room temperature are investigated. The non‐monotonic character of the variation of the ω‐phase volume fraction has been demonstrated for an increasing number of turns; in particular, the HPT processing of 1 turn leads to the precipitation of 10% ω‐phase from the β‐matrix, but at 10 turns of HPT a reverse phase transformation is observed. It is shown that nanostructure formation with a minimum content of the ω‐phase allows for achievement of significant strengthening in the alloy while preserving a relatively low elastic modulus. Abstract : In this paper, the possibility of a significant enhancement of strength, while preserving a low elastic modulus, is demonstrated. The obtained results are very important for the medical application of the Ti‐15Mo alloy.